Penerapan Nilai-Nilai Pendidikan Politik Dan Etika Pesantren Dalam Pembentukan Karakter Kepemimpinan Santri Di Pondok Pesantren Adnan Al-Charish - Fiza Ikromulloh; Sri Minarti (CV. ITTC INDONESIA, 2026)
This study aims to analyze the implementation of political education values and Islamic boarding school ethics in shaping the leadership character of students at Adnan Al-Charish Islamic Boarding School. Political education within the pesantren environment plays a strategic role in forming students who possess ethical political understanding, polite social attitudes, and the ability to respond wisely to various social and political issues. In addition, pesantren ethics emphasizing obedience to Allah and teachers, discipline, responsibility, cooperation, and simplicity serve as essential foundations in developing students’ leadership character. This study employed a qualitative approach using library research methods. The data sources were obtained from various literature materials, including books, scientific journals, articles, and relevant documents related to the research topic. Data analysis techniques were conducted through data collection, reduction, presentation, and conclusion drawing. The results of the study indicate that Adnan Al-Charish Islamic Boarding School integrates political education values through student organizational activities, deliberation practices, religious studies, and the exemplary leadership of the kiai in daily life. Furthermore, pesantren ethical values such as honesty, trustworthiness, responsibility, and simplicity are implemented as efforts to shape students’ leadership character. However, several challenges remain, including students’ limited understanding of practical politics and the influence of external social environments. This study concludes that the implementation of political education values and pesantren ethics contributes significantly to the formation of students’ leadership character. Therefore, continuous strengthening and development of these values are necessary to create a generation of students who possess integrity, noble character, and strong leadership qualities.